Seismic Vulnerability of Semarang, Indonesia for Shallow Crustal Fault Earthquake - Partono, Windu; Irsyam, Masyhur; Asrurifak, Muhammad; Sari, Undayani Cita; Victor, Victor (Indonesian Journal of Geography, 2025)
In 2017, the National Centre for Earthquake Studies of Indonesia released the distribution of 25 shallow crustal fault lines throughout the island of Java in Indonesia and four of them (Semarang, Demak, Rawapening and Weleri fault lines) are located around the city of Semarang. The presence of four shallow crustal fault earthquake sources, has led to the need to understand the potential earthquake hazards of Semarang through the development of earthquake-microzoning maps. Earthquake-microzoning maps of Semarang should be developed with reference to the Indonesian earthquake hazard maps and based on the deterministic and probabilistic seismic hazard approaches. Through the development of earthquake-microzoning maps, it is possible to estimate the areas with the highest and lowest surface-shaking (peak ground acceleration). The earthquake-microzoning maps based on the Semarang and Demak fault earthquake scenarios provide a preliminary indication that buildings constructed using the Indonesian Seismic Code (SNI 1726:2002) will experience stronger surface-shaking if the earthquake magnitude from both sources is at least M5.5. The results of the analysis for the creation of earthquake-microzoning maps based on the Rawapening and Weleri fault earthquake scenarios provide a preliminary indication that buildings constructed using SNI 1726:2002 are expected to experience slightly weaker ground-shaking if the earthquake magnitude from both sources reaches a maximum of M6.5. All buildings constructed in this area using SNI 1726:2012 and SNI 1726:2019 are expected to experience weaker surface-shaking due to the four earthquake source scenarios with a maximum magnitude of M6.5.